Augmented Reality to Induce Enjoyment in Edutainment Mobile Game - Oo Yew Beng Keat; Noorhaniza Wahid; Norhanifah Murli; Rahayu A. Hamid (JOIV : International Journal on Informatics Visualization, 2018)
Augmented reality (AR) is a technology that overlay the computer generated image on real world object. AR has been implemented in various fields and one of the fields is edutainment-based game. Edutainment-based game is a game designed to make the learning process become more fun. Among the edutainment gameplay genre such as tile-matching, action puzzles, traditional puzzle games, and hidden object. However, there are still a lack of edutainment gameplay that utilizes AR technology for hidden object game genre. The hidden object game in the market today does not use 3D scene as their background. Therefore, the objective of this project is to develop an AR edutainment game in 3D scene view by using hidden object puzzle genre. This edutainment game can be used as an alternative edutainment teaching aids in kindergarten and primary school. Player’s enjoyment is measured based on the evaluation of user acceptance level towards the gameplay, functionality and performance level. Results of user testing shows that 67% of the total respondents strongly agreed that this game is enjoying to be played. In addition, there are 53% of the respondents agreed that the game is stable when being played in a mobile device. Next, there are 67% of the respondents agreed that the presentation of the information and instruction are clear.